Islamic Retirement Planning Among Indonesian Bankers - Syamlan, Yaser Taufik; Easti, Reti Rahma (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This study aims to analyze differences in demographic factors towards retirement planning behavior according to Islamic perspective. This research wants to analyze the influence of clarity of purpose, retirement attitude and potential conflict towards retirement planning behavior according to among the Muslim who is working in a conventional bank and the Islamic Bank. The sample used in this study as many as 270 respondents of both conventional & Islamic Banker in Indonesia. There are two methods that are used in this research which are ANOVA and Multiple Linear Regression. The results identified several demographic variables that were significant such employment status (either working in the conventional bank or Islamic Bank) and income level. Furthermore, some demographic variables do not significant including age, number of dependents and level of education. This research also shows that non-demographic variables such as clarity of purpose, retirement attitudes and potential conflicts affect significantly to influence the behavior of bankers in retirement planning according to Islamic perspective. In conclusion, the conventional Muslim bankers know that they should manage their retirement according to the Shariah value. However, some of them didn’t believe that the Shariah investment instrument can fulfill their desired retirement goals.